Islamic philanthropy and development in Zamfara state: an assessment of zakat administration structures and outcomes - Bello, Muhammad; Usman, Nasir M. (Journal of Social Review and Development, 2025)
A fundamental tool for income transfer and poverty reduction in Muslim communities, zakat is one of the five pillars of Islam. In Zamfara State, the institutionalization of zakat followed the introduction of Sharia law in 2000, leading to the formation of both state-run and private Islamic philanthropic entities. This study explores the organization, administration, and developmental results of zakat in Zamfara, relying mainly on secondary sources including official papers, policy reports, NGO publications, and current scholarly literature. Through qualitative content analysis, the study finds that while zakat structures exist in many forms, difficulties such as inadequate transparency, inconsistent distribution systems, and insufficient recordkeeping have impeded their developmental impact. Nonetheless, stories of successful initiatives in sectors like education and social welfare highlight the potential of zakat as a tool for inclusive development. The study concludes by suggesting improvements in administration, increased accountability, and stronger integration of Islamic charity ideals with modern development tactics.